2015
DOI: 10.1016/j.jds.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zoledronic acid on osteoblasts in three-dimensional culture

Abstract: International audienceBackground/purpose: Bisphosphonates (BPs) are synthetic drugs with antitumorand bone antiresorptive activities. The use of BPs is suspected to favor the emergence of osteonecrosisof the jaw (ONJ), a putative side effect whose pathogenesis remains unclear. Thus,we aimed to get insights about the impact of BPs on osteoblasts functions, using a threedimensional(3D) culture model, which is suggested to be more similar to the in vivo tissuesthan monolayers.Materials and methods: Effects of low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Such experimental set up, i.e. using spherical or quasi‐spherical spheroids, is fundamental for drug screening, as previously reported by different researchers …”
Section: Resultsmentioning
confidence: 97%
“…Such experimental set up, i.e. using spherical or quasi‐spherical spheroids, is fundamental for drug screening, as previously reported by different researchers …”
Section: Resultsmentioning
confidence: 97%
“…Three publications investigated the role of osteoblasts in bone remodelling and their contribution to MRONJ development. High ZA concentrations were shown to both decrease proliferation levels [24,26,30] and increase apoptosis [26] in osteoblasts. Furthermore, medium conditioned by ZA-treated epithelial cells was able to decrease proliferation and expression of factors (BMP-4, TGF-β2 and ALP) in osteoblasts, suggesting soft tissue involvement in activation of bone remodelling and reduced bone formation ability (A7).…”
Section: Discussionmentioning
confidence: 98%
“…A total of 11 publications were included in this review (see Figure 2). All of the included studies were in vitro studies: five studies concern oral epithelial cells [20][21][22][23][24], six studies are about oral fibroblasts [20][21][22][25][26][27], three studies are about endothelial cells [23,28,29], three studies are about osteoblasts [24,26,30] and one study is about dental pulp stem cells (DPSC) [25]. The included 11 articles were further quality-assessed according to the aforementioned model.…”
Section: Study Selectionmentioning
confidence: 99%
“…Previously, Huang et al and Thibaut et al reported a significant cytotoxic effect on MC3T3-E1 cells and human foetal osteoblasts (hFOBs) with concentrations of ZA higher than 10 μM. 15,16 This may suggest that the negative effect of ZA on cell viability is only significant at concentrations higher than the therapeutic dose. The in vivo study by Pozzi et al supports this notion where it was shown that therapeutic doses of ZA decreased the numbers of osteoblasts per bone perimeter in mice without any statistical significance being reached.…”
Section: Discussionmentioning
confidence: 99%